Optimization of Radiation Dose and Effective Dose for CT Pelvis Examinations in Main Hospitals in ALTaif Region - AlQahtani, Khaled Shaher; al wathnani, Khaled nami; Alghamdi, Rami mohammed; Alghubayshi, Ahmed Yaseen; almalki, Saif hassen; Aleyli, Abdulwahab Aali; Alotaibi, Ahmed Eid; Altowairqi, Fahad Musilh; Al-Subaie, Mufleh Mohammed; Alahmary, Waleed Saeed; Dhafiri, Fahad Mohammed (Journal of Ecohumanism, 2024)
Introduction: CT scan is one of the medical imaging methods that irradiate patients with significant amounts of radiation. These amount of radiation doses must be well estimated if the imaging area is in part containing radiation-sensitive organs such as the pelvic area. Objectives: the objectives of the current study were to assess radiation dose during pelvis and Abdomen CT imaging and estimate the effective dose as well as to propose diagnostic reference level (DRL).Methodology: 200 adult patients irradiated in two major governmental hospital in Taif city, Saudi Arabia, patients’ demographic data from was collected such as weight, height, and age. Scanner specifications and scan parameters for each pelvis examination were recorded in special data collection sheet. Volume CT dose index (CTDIvol and dose length product (DLP) were utilized to estimate the radiation dose and effective dose. Microsoft Excel was used to analyse the data.Main Results: there was variation in scanning parameters among two hospitals under study and this result in variation in effective dose between two hospitals. The average DLP, CTDIvol and effective dose were 368.5, 390.7 mGy-cm,10.2,10.8 mGy and 7, 7.4 mSv for hospital one and two respectively. Conclusion: Based on the third quartile of DLP and CTDIw, the recommended DRL for both hospitals was 405 mGy-cm and 21.75 mGy, respectively. The findings revealed a reduced effective dose value when compared with previous studies.